An Introduction to the Complexity Class of Pure Nash Equilibrium - Wirz, Victor Hugo; Moura, Pedro Nuno (Anais do Encontro de Teoria da Computação (ETC); 2023: Anais do VIII Encontro de Teoria da ComputaçãoDO - 10.5753/etc.2023.229527, 2023)
Taxonomy of problems in Computer Science has been typically done with formulations as decision problems. This approach is inadequate for many search problems of interest when the structure of the instance in itself guarantees the existence of a positive certificate. In this paper, we provide an introduction to the class of problems PLS and its connections with finding Pure Nash Equilibrium in Congestion Games.